Understanding of Simple Financial Statement Recording for AL- Ikhlas Mosque Block VI Griya Martbung - Siti Aisyah; Ridho Gilang Adiko; Ratih Anggraini Siregar; Purwitha Sari; Tonna Balya (JUDIMAS, 2021)
This community service is carried out to provide new understanding and insight for members of the management of the Al-Ikhlas Martubung mosque in recording financial reports regularly, properly and correctly every month. It is intended that the resulting financial information can be used by information users such as the surrounding community and the local government to monitor the inflow and outflow of mosque finances. This is considered important because the funds that enter the mosque's treasury are not only from community alms, but there is assistance from the local government for the construction of mosques and improvement of facilities. For this reason, it is important to feel that it is necessary to record financial statements on a regular basis for every financial transaction that occurs so that the financial information submitted can be justified. After training in recording financial reports to the administrators of the al-ikhlas mosque, the results are obtained if the members of the mosque management now understand and understand how to do good and correct financial records every month.